One implementation of the Chi Square Test with SPSS - Tinoco Gómez, Oscar (2008)
Chi Cuadrado illustrates the use of the statistical software SPSS applied to the test to prove independence between two variables. The application carries out in the evaluation of the impact generated in the educational page of the Faculty of Administrative Sciences of the National University Federico Villarreal in relation to the use of some of the tools of the technologies called of information and communication in the process of formation profesional.